EVALUASI PLT BIOGAS TERANTAM COVERED LAGOON (CAL) 700 KW UNTUK PENGEMBANGAN PLT BIOGAS TIPE CSTR - Rosyadi, Erlan; Rahmawati, Nurdiah; Pertiwi, Astri; Murti, Galuh Wirama; Fauzan, Naazi; Rini, Tyas Puspita; Muharto, Bambang; Bhaskara, Arya; Saputra, Hens (Majalah Ilmiah Pengkajian Industri, 2019)
Production of Crude Palm Oil (CPO) is increasing from year to year and is predicted to reach 41.6 million tons per year in 2018. Each ton of CPO will produce 3,28 m3 of POME during the production process. Improper handling of POME, besides causing soil pollution and flying, will release methane gas that categorized as GHG. BPPT cooperate  with PTPN V utilized POME to produce biogas and then be converted into electricity in a Biogas Power Plant (PLTBg) in Terantam with a design capacity of 700 kW. The reactor used is a closed Anaerobic Lagoon (CAL) reactor equipped with a recirculation pump. From the evaluations, the technology chosen was not optimal from the operation, its evaluaed from the accumulation of cakes and sludge collected in the reactor which could be disturb during an anaerobic reaction. The next technology development will be carried out with the development of PLTBg in Sei Pagar using CSTR technology. At the same reactor capacity, CSTR has a faster HRT compared to CAL. CSTR is also easier in control of pH and temperature, also requires less land.Keyword : POME, Biogas, CSTR, Covered Lagoon, HRT, OLR